Characterization of the rescued “Voghera” sweet pepper landrace grown in northern Italy - Cavagna, P.; Camerini, G.; Fibiani, M.; Andreani, L.; Cella, R.; Concia, L.; Lo Scalzo, R. (Spanish Journal of Agricultural Research, 2012)
A traditional Italian sweet pepper landrace, ‘Peperone di Voghera’, which faced the risk of extinction, was analyzed for its genetic, phenological, morphological, agronomic and biochemical traits. An extant population was compared with cultivars ‘Quadrato d’Asti’, ‘Cuneo’, and ‘Giallo d’Asti’, cultivated in the same area, in order to evaluate the chance of the landrace recovery. Amplified fragment length polymorphism (AFLP) analysis demonstrated that Voghera landrace is distinct with respect to reference cultivars, thus excluding extensive genetic contamination and providing a molecular basis of both phenological and biochemical differences. Leaf chlorophyll content is lower, fruits start ripening earlier than controls, and yield (1100-1300 g plant-1) does not significantly differ. Sensitivity to root pathogens, the main factor that led to the decline in the past, does not seem to compromise the future chance of recovery. Vitamin C concentration is high (200-240 mg/100 g) and preserved by cold storage; more than 25% of vitamin C is also kept in pickled fruits. ‘Voghera’ landrace has nutritional and gastronomic properties that can be appreciated by consumers. The high internal genetic variability shown by AFLP analysis indicates that future selection work is necessary to fully maintain the original traits of the landrace and to improve it.